Effect of Suryanamaskar on Stress in Delayed-Postpartum Indian Women - A Pilot Study - Devanshi Gala; J. K. Savalia (Dr. Chinmay Pandya, 2022)
Motherhood, though emotionally fulfilling, is physically and mentally challenging, that changes the women's overall life. Hence, the perinatal period, in general as a whole, can be considered an extremely vulnerable period. Which includes layers of stressors like the skin of an onion. The present study was designed to assess the effect of the Suryanamaskar on stress in delayed-postpartum in Indian women. Method: 39 participants, enrolled using convenient sampling, were divided into 3 groups of 13 participants each. Group 1 was given a fast-paced Suryanamaskar module; Group 2 was given a slow-paced Suryanamaskar module; and Group 3 was given no intervention. Maternal Perceived Stress Scale (MPSS) questionnaire was used for data collection and paired t-test was used for analysis. Results: A very significant decrease was seen in the levels of stress in delayed-postpartum women of Group 1 (p<0.05), and Group 2 (p<0.01), and Groups 1 and 2 combined (p<0.01) after practicing the Suryanamaskar-based intervention; while no significant change was recorded in women of Group 3 (control group). Conclusion: Regular practice of the Suryanamaskar, even if has been practiced for a short duration, helps to reduce stress levels in delayed-postpartum women.